Perkuliahan Daring (E-Learning): Studi Kepuasan Mahasiswa FIKOMM Universitas Mercu Buana Yogyakarta - SUGIARTO, RENO; Archiles, Michael Fransisco; Yuristiawan, Miko; Nastain, M.; Fariha, Naela Faza (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
E-learning is a medium for lectures that can be run remotely and can be accessed anytime and anywhere, which means it is flexible, this can facilitate access to lectures for both teaching staff and students. Service Quality is a method that is suitable to be used as a determinant of the high level of satisfaction with the implementation of online lectures. The main focus of the research will aim to determine student satisfaction rates for students from the Faculty of Communication and Multimedia, Mercu BuanaUniversity, Yogyakarta, regarding the implementation of online lectures and also serve as evaluation material and input for the campus regarding implementationthis e-learning.In the research method used is the quantitative descriptive method.Theresults of this research, students from the Faculty of Communication and Multimedia, Mercu Buana University, Yogyakarta, have a high level of satisfaction with the online lecture process (E-Learning), this can be seen in the satisfaction indicators which consist of Reliability and Responsiveness IndicatorsMeanwhile, on the Assurance and Empathy Indicators, students have a fairly satisfactory level of satisfaction.